Outcomes and timing of endoscopic retrograde cholangiopancreatography for acute biliary pancreatitis. Issue 9 (September 2019) - Halász, Adrienn; Pécsi, Dániel; Farkas, Nelli; Izbéki, Ferenc; Gajdán, László; Fejes, Roland; Hamvas, József; Takács, Tamás; Szepes, Zoltán; Czakó, László; Vincze, Áron; Gódi, Szilárd; et al.
Abstract: Background: Indication of endoscopic retrograde cholangiopancreatography (ERCP) in acute biliary pancreatitis (ABP) is challenging. Aims: In this retrospective study, we analyzed real-world data to understand the ERCP practice in ABP in Hungarian centers. Methods: Clinical data on ABP patients (2013–2015) were extracted from our large multicentric database. Outcomes, quality indicators and the role of early timing of ERCP (<24 h from admission) were analyzed. Results: There were 356 patients with ABP. ERCP was performed in 267 (75%). Performance indicators of ERCP proved to be suboptimal with a biliary cannulation rate of 84%. Successful vs unsuccessful cannulation of naïve papilla resulted in lower rates of local [22.9% vs 40.9%, (P = 0.012)] and systemic [4.9% vs 13.6%, (P = 0.042)] complications. Successful vs unsuccessful clearance resulted in lower rates of local complications [22.5% vs 40.8%, (P = 0.008)]. Successful cannulation and drainage correlated with less severe course of ABP [3.6% vs 15.9%, (P = 0.001) and 4.1% vs 12.2%, (P = 0.033)] respectively. A tendency of an increased rate of local complications was observed if ERCP was performed later [<24 h: 21.1% (35/166); between 24–48 h: 23.4% (11/47); >48h: 37.2% (16/43) (P = 0.088)]. Conclusion: Optimization of ERCP indication in ABP patients is critical as suboptimal ERCP practices in ABP without definitive stone detection are associated with poorer clinical outcomes.